Degradation of mirubactin to multiple siderophores with varying Fe(iii) chelation properties. Issue 25 (15th June 2022) - Pu, Hong; Jiang, Ting; Peng, Dian; Xia, Juanjuan; Gao, Juan; Wang, Yeji; Yan, Xiaohui; Huang, Xueshuang; Duan, Yanwen; Huang, Yong
Abstract : Three siderophores mirubactins B–D (4–6 ) were identified as the degradation products of previously isolated mirubactin (1 ) and 4 contains an unusual cyclic amidine functionality. Cyclic voltammetry showed that 5 and 6 have reduced iron complexing capacity. Abstract : Three siderophores mirubactins B–D (4–6 ) were identified as the degradation products of previously isolated mirubactin (1 ). Their structures were revealed by HR-ESI-MS/MS, NMR analyses, and density functional calculations, among which 4 contains an unusual cyclic amidine functionality. Cyclic voltammetry showed that 5 and 6 have reduced iron complexing capacity. Mirubactin (1 ) and Fe(iii ) could also form a stable complex, which may be an ingenious approach to compete for iron acquisition by the producing organisms.